"Can you send us a PM please?" Service recovery interactions on social media from the perspective of organizational legitimacy. (December 2020) - Van Herck, Rebecca; Decock, Sofie; De Clerck, Bernard
Abstract: Drawing on a discursive approach to legitimation (Erkama and Vaara, 2010; Higgins and Walker, 2012; Glozer et al., 2019), this study investigates the (de)legitimation strategies used by companies and (potential) customers in private and public CMC complaint communication, and the interactional dynamics between them. Using the Aristotelian framework of persuasive appeals ethos, logos, and pathos, we analysed (1) 91 emails (replies to complaints from a varied sample of large UK companies), (2) 91 customer reactions to these replies on companies' public Facebook pages and Twitter, and (3) 383 additional comments to these posts made by the company, the customer, and other stakeholders. The results reveal a clear shift in companies' private versus public discourse: While they mainly seek legitimacy in email replies by substantiating their complaint decision (logos) and by accommodating to the customers' feelings (pathos and ethos), their social media interventions are mainly about redirecting customers to a private channel to avoid having to deal with the transactional side of complaint handling in public. Customers, in their turn, delegitimate these companies by primarily criticizing companies' service failures and service recovery efforts (ethos) and – to a lesser extent – by defending their case (logos) and expressing negative emotions (pathos). In terms of interactional dynamics, the results show that companies are not comfortable with implementing a dialogic approach. Their attempts at discursive finalization, i.e., silencing consumers' negative feedback, clearly expose social media agents' lack of agency and power to build up relationships with customers and perform adequate service recovery.